Pengaruh Latihan Double Leg Speed Hop Terhadap Power Otot Tungkai Atlet Karate Dojo Kodim 1001 Amuntai - Mahmudah, Mahmudah; Dirgantoro, Edwin Wahyu; Arifin, Syamsul (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
The sport of karate is a form of self-defense and is considered a discipline that facilitates physical and mental balance and improves health. The sport of karate also requires a good physical condition, because physical condition is the foundation of sports achievement. Plyometric training has proven to be an effective method for improving a number of physical qualities such as strength and jump height. The purpose of this study was to determine the effect of Double Leg Speed Hop Exercise on leg muscle strength of Dojo Kodim 1001 Amuntai participants. The methodology used is one group pretest-posttest design using pre-experiment design and quantitative approach. the use of data collection methods before and after the test. Using SPSS 23, data analysis procedures include homogeneity test, normality test, descriptive statistics, and hypothesis testing. The results obtained from testing using mean scores, data analysis and hypothesis testing resulted in findings that increased significantly from 150.73 to 155.47. Using the sign. (2-tailed) of 0.000 <0.05 obtained from the hypothesis test, it can be concluded that Hα is accepted and Ho is rejected. Based on the computational findings and descriptive statistical values of the pre and post tests, it can be concluded that the Double Leg Speed Hop exercise has an influence on the ability of Dojo Kodim 1001 Amuntai players to increase leg muscle strength in karate sports.